1981
DOI: 10.2527/jas1981.52163x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Serum Somatomedin-Like Activity and Fibroblast Proliferative Activity with Age and Body Weight Gain in Sheep

Abstract: The relationship between serum growth factors and body weight gain was examined in five Dorset lambs. The lambs were weighed and bled by jugular puncture at 2-week intervals between 2 and 18 weeks of age. Somatomedin-like activity (Sm) declined from initially high concentrations at 2 weeks to fairly constant concentrations between 6 and 18 weeks. Relative weight gain--i.e., gain expressed as a percentage of body weight--declined in a manner similar to that of Sm. Mean relative weight gain and mean Sm for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…This observation held true over the broad range of mean IGF-1 levels detected and is consistent with previous observations in both ruminants and non-ruminants (Davis et al, 1984;Breier et al, 1986). The data presented in Figure 2b suggest that serum IGF-1 levels are not correlated with slaughter weight in the ram and are consistent with those of Olsen et al (1981) and Medrano and Bradford (1991).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This observation held true over the broad range of mean IGF-1 levels detected and is consistent with previous observations in both ruminants and non-ruminants (Davis et al, 1984;Breier et al, 1986). The data presented in Figure 2b suggest that serum IGF-1 levels are not correlated with slaughter weight in the ram and are consistent with those of Olsen et al (1981) and Medrano and Bradford (1991).…”
Section: Discussionsupporting
confidence: 91%
“…Davis et al (1984) emphasized that the episodic pattern of GH secretion makes it difficult to determine a relationship between GH concentrations and body growth variables. Previous research detected small positive correlations between body weight and serum somatomedin-like activity in lambs (Olsen, Wangsness, Patton and Martin, 1981). Previous research detected small positive correlations between body weight and serum somatomedin-like activity in lambs (Olsen, Wangsness, Patton and Martin, 1981).…”
Section: Discussionmentioning
confidence: 91%
“…This pattern of increasing serum IGF-I levels during postnatal growth has been reported in pigs (Scanes, Lazarus, Bowen et al 1987), man (Furlanetto et al 1977) and rats (Daughaday, Parker, Borowsky et al 1982). Olsen, Wangsness, Patton & Martin (1981) reported a highly significant correlation between the total serum IGF level and relative weight gain in lambs. Lund-Larsen, Sundby, Kruse & Velie (1977) reported a similar relationship with rate of weight gain in Red Danish bulls.…”
Section: Discussionmentioning
confidence: 71%
“…From this initial report, numerous publications have appeared describing the clinical relevance of IGF-I concentrations in the evaluation of disease states of short stature, growth hormone excess, and nutritional status (Underwood, 1985). A few earlier human studies reported some positive correlations between IGF-I concentrations and growth rates (Gourmelen et al, 1986;Rappaport et al, 1987), but there is no consistent evidence in the literature, even in a recent IGF-I review (Daughaday and Rotwein, 1989), that a positive correlation exists between IGF-I and growth rate in normal individuals.…”
Section: Resultsmentioning
confidence: 99%